Пайпер и сила снов - Зеппа Шейна Малдун (Disney. Академия грез, 2017)
Экземпляры: ф-4 (20180723) / Инвентарный номер: 52314 / Цена: 161.00 / Сис.шифр: И(Амер) / Авт.знак: З-56 / ГРНТИ: 17.82.93 / ББК: 84(7Coe)-44